Active operations of commercial banks improving management strategy - Kholmuradov Musurmon Avlakulovich (THE INNOVATION ECONOMY, 2026)
Ensuring the quality of asset portfolios of commercial banks, the need to ensure their financial stability and liquidity is considered one of the current issues. In this scientific article, an attempt was made to develop a scien tific proposal and practical recommendations on ways to increase the efficiency of the assets of commercial banks